2007
DOI: 10.1088/0957-0233/18/2/s11
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of a commercial AFM: traceability for a coordinate system

Abstract: Traceability of measurements and calibration of devices are needed also at the nanometre scale. Calibration of a commercial atomic force microscope (AFM) was studied as part of a dimensional nanometrology project at MIKES. The calibration procedure and results are presented here. The metrological properties of the AFM were characterized by several measurements. A method developed to calibrate the z scale by a laser interferometer during a normal measurement mode of an AFM is presented. x and y movements were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…1, which defines the coordinate system of the instrument. Experience in characterizing mSPMs at other metrology institutes [4][5][6][7][8][9] has shown that the metrological frame is the dominant source of measurement uncertainties arising from alignment errors, particularly Abbé errors and nonorthogonality of the measurement axes, and environmental vibration. To achieve the target total uncertainty of dimensional measurements, minimizing these contributions is a principal consideration in the design of the metrological frame and the material selected for its construction.…”
Section: System Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…1, which defines the coordinate system of the instrument. Experience in characterizing mSPMs at other metrology institutes [4][5][6][7][8][9] has shown that the metrological frame is the dominant source of measurement uncertainties arising from alignment errors, particularly Abbé errors and nonorthogonality of the measurement axes, and environmental vibration. To achieve the target total uncertainty of dimensional measurements, minimizing these contributions is a principal consideration in the design of the metrological frame and the material selected for its construction.…”
Section: System Integrationmentioning
confidence: 99%
“…1,2 The challenge in realizing this mSPM concept is to create a macroscopic mechanical instrument capable of traceable dimensional measurement at the nanoscale with a combined uncertainty of less than 1 nm. Experience in designing ultraprecision mechanical stages and instruments 3 and in operating similar mSPMs at other metrology institutes [4][5][6][7][8][9] has shown that there are many contributions to the uncertainty of the displacement measurements. These include alignment errors (particularly Abbé errors 10 ), deformations of the mechanical structures (for instance, due to thermal expansion), motion errors of the translation stage, form errors of the interferometer mirrors, nonlinearities of the interferometers, and fluctuations in the refractive index of air.…”
Section: Introductionmentioning
confidence: 99%
“…7 These include noise characterization, lateral and vertical scale calibration, deviation from flatness calibration, and orthogonality error characterization. 8,9 Traceable calibration, measurement modeling, and uncertainty analysis are needed to analyze the uncertainty in a measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Traceability of the interferometric position measurement is secured through the laser source which should operate on one of the wavelengths coinciding with transitions in a suitable absorbing media [3]. Stable optical frequency represents stable wavelength in vacuum; in atmospheric conditions conversion to precise wavelength needs an evaluation of the refractive index.…”
Section: Introductionmentioning
confidence: 99%